Multiancestry Genome-Wide Association Study of Aortic Stenosis Identifies Multiple Novel Loci in the Million Veteran Program. Issue 12 (20th February 2023) - Small, Aeron M.; Peloso, Gina M.; Linefsky, Jason; Aragam, Jayashri; Galloway, Ashley; Tanukonda, Vidisha; Wang, Lu-Chen; Yu, Zhi; Sunitha Selvaraj, Margaret; Farber-Eger, Eric H.; Baker, Michael T.; Setia-Verma, Shefali; et al.
Abstract : Background: Calcific aortic stenosis (CAS) is the most common valvular heart disease in older adults and has no effective preventive therapies. Genome-wide association studies (GWAS) can identify genes influencing disease and may help prioritize therapeutic targets for CAS. Methods: We performed a GWAS and gene association study of 14 451 patients with CAS and 398 544 controls in the Million Veteran Program. Replication was performed in the Million Veteran Program, Penn Medicine Biobank, Mass General Brigham Biobank, BioVU, and BioMe, totaling 12 889 cases and 348 094 controls. Causal genes were prioritized from genome-wide significant variants using polygenic priority score gene localization, expression quantitative trait locus colocalization, and nearest gene methods. CAS genetic architecture was compared with that of atherosclerotic cardiovascular disease. Causal inference for cardiometabolic biomarkers in CAS was performed using Mendelian randomization and genome-wide significant loci were characterized further through phenome-wide association study. Results: We identified 23 genome-wide significant lead variants in our GWAS representing 17 unique genomic regions. Of the 23 lead variants, 14 were significant in replication, representing 11 unique genomic regions. Five replicated genomic regions were previously known risk loci for CAS ( PALMD, TEX41, IL6, LPA, FADS ) and 6 were novel ( CEP85L, FTO, SLMAP, CELSR2, MECOM, CDAN1 ). Two novel lead variants were associated in non-White individuals ( P <0.05): rs12740374 ( CELSR2 ) in Black and Hispanic individuals and rs1522387 ( SLMAP ) in Black individuals. Of the 14 replicated lead variants, only 2 (rs10455872 [ LPA ], rs12740374 [ CELSR2 ]) were also significant in atherosclerotic cardiovascular disease GWAS. In Mendelian randomization, lipoprotein(a) and low-density lipoprotein cholesterol were both associated with CAS, but the association between low-density lipoprotein cholesterol and CAS was attenuated when adjusting for lipoprotein(a). Phenome-wide association study highlighted varying degrees of pleiotropy, including between CAS and obesity at the FTO locus. However, the FTO locus remained associated with CAS after adjusting for body mass index and maintained a significant independent effect on CAS in mediation analysis. Conclusions: We performed a multiancestry GWAS in CAS and identified 6 novel genomic regions in the disease. Secondary analyses highlighted the roles of lipid metabolism, inflammation, cellular senescence, and adiposity in the pathobiology of CAS and clarified the shared and differential genetic architectures of CAS with atherosclerotic cardiovascular diseases.